2014
DOI: 10.1007/s11136-014-0795-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and socio-dental impact among underprivileged Brazilian adolescents

Abstract: Individual and contextual variables were related to the OIDP and QL in underprivileged Brazilian adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 35 publications
8
30
1
2
Order By: Relevance
“…In addition, systematic literature reviews have already proved the negative effect of some oral problems, such as tooth loss 6 and dissatisfaction with the teeth and mouth 7 on the oral health-related quality of life. As in the present study, previous studies conducted in Brazilian cities among children and adolescents have identified a greater impact captured by the OIDP among those with compromised periodontal conditions 26 and tooth pain 23 . Additionally, malocclusion was associated with a greater impairment of oral health-related quality of life among English adolescents 24 .…”
Section: Discussionsupporting
confidence: 77%
“…In addition, systematic literature reviews have already proved the negative effect of some oral problems, such as tooth loss 6 and dissatisfaction with the teeth and mouth 7 on the oral health-related quality of life. As in the present study, previous studies conducted in Brazilian cities among children and adolescents have identified a greater impact captured by the OIDP among those with compromised periodontal conditions 26 and tooth pain 23 . Additionally, malocclusion was associated with a greater impairment of oral health-related quality of life among English adolescents 24 .…”
Section: Discussionsupporting
confidence: 77%
“…Diferenças regionais no acometimento de outros agravos e doenças bucais, tais como cárie 35 e fluorose dentária 36 , entre crianças brasileiras tem sido identificada em estudos prévios. Ressalta-se ainda que tanto as desigualdades sociais, como a presença de agravos bucais, podem comprometer a qualidade de vida e impactar negativamente na vida diária das pessoas 37 . Ao considerar a totalidade das crianças de 12 anos incluídas no SB Bra-sil 2010, foi identificada em estudo prévio 14 a inexistência de diferenças significativas no acometimento de oclusopatias graves entre as regiões brasileiras, mas sim diferenças entre as cidades.…”
Section: Discussionunclassified
“…Data about parents' perception about their children health and the socio-economic conditions were obtained by means of questionnaires sent to the schoolchildren's parents. The questions were of multiple choice, and we used a previously validated questionnaire used in other studies in the literature assessing underprivileged children and their parents 1,13,16,20,21 . This instrument presented questions on the parent's perceptions of School performance and oral health conditions 53 general health, oral health, oral hygiene and school performance of their children (with response options: 'excellent', 'very good', 'good', 'fair', 'bad').…”
Section: Methodsmentioning
confidence: 99%
“…Oral problems can cause strong impact on the functional, emotional, and social aspects of children and adolescents. Maintenance of the oral health of this population, however, still represents a great challenge to professionals and health systems around the world. Whereas a large proportion of this population is engaged in activities in the school context, one has to consider the possibility that the school performance of these schoolchildren may be affected by several factors, such as psychological, socio‐economic, family environment and also clinical conditions.…”
Section: Introductionmentioning
confidence: 99%